Conventional vs computed radiography: evaluation of myelography. - Yang, P J; Seeley, G W; Carmody, R F; Seeger, J F; Yoshino, M T; Mockbee, B (American Journal of Neuroradiology, 1988)
A prospective study was performed to compare the diagnostic efficacy of conventional film-screen (FS) imaging with computed radiography (CR) in myelography. Forty examinations were done with both methods. Digital myelography was found to have diagnostic accuracy equal to that of conventional film-screen examinations.